Design and Development of Clarithromycin Floating Pellets Using Sodium Alginate and HPMC - Bhuiya, Md Abdul Motaleb; Mazumder, Kishor; Dewan, Irin; Mamun, Md Elias Al (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The purpose of our study was to achieve the gastro-retentive delivery of Clarithromycin by producing floating pellets to get a better therapeutic effect against gastrointestinal ulcers mostly caused by Hedyotis pylori. Thereby Clarithromycin floating pellets were prepared by utilizing the blending of polymers such as Sodium (Na) Alginate and Hydroxy Propyl Methyl Cellulose (HPMCK4M & HPMC K100LV). The HPMC-alginate blend containing Clarithromycin produced a hydrogel bead that was able to show buoyancy in the simulated gastric fluid. The pellets showed more than 8 hours of buoyancy depending on their polymeric ratio. In addition to the buoyancy test, several other tests like floating time (upto 12 hrs with increasing Na-Alginate), contraction ratio, particle size analysis, were performed that showed the development of acceptable floating pellets. Furthermore, SEM was performed on the prepared Clarithromycin pellet to assess their morphological characteristics. Clarithromycin floating pellets with 1.5% Na-alginate & HPMC K4M: HPMC K100LV (1:2) give the better formulation and produce pharmaceutically acceptable parameters. Dhaka Univ. J. Pharm. Sci. 21(1): 25-31, 2022 (June)